2,6-Dimethylanilinium chloride monohydrate - Smirani, Wajda (International Union of Crystallography, 2008)
In the title hydrated molecular salt, C(8)H(12)N(+)·Cl(−)·H(2)O, the component species interact by way of N—H⋯O, N—H⋯Cl and O—H⋯Cl hydrogen bonds, resulting in a three-dimensional network.